2012
DOI: 10.1139/h11-159
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional microarray design reveals the response to obesity is largely tissue specific: analysis of common and divergent responses to diet-induced obesity in insulin-sensitive tissues

Abstract: Obesity is a chronic condition involving the excessive accumulation of adipose tissue that adversely affects all systems in the body. The aim of the present study was to employ an unbiased, genome-wide assessment of transcript abundance in order to identify common gene expression pathways within insulin-sensitive tissues in response to dietary-induced diabetes. Following 20 weeks of chow or high-fat feeding (60% kcal), age-matched mice underwent a euglycemic-hyperinsulinemic clamp to assess insulin sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Others have also shown higher numbers of adipose tissue differentially expressed genes (DEGs) compared to liver, both in response to fasting [42], and during LPS-induced inflammation [43]. Most recently, high-fat feeding has been shown to induce obesogenic gene expression changes in 4 murine tissues, with adipose tissue producing the second highest number of DEGs in the following order: skeletal muscle > adipose > liver > heart [44]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also shown higher numbers of adipose tissue differentially expressed genes (DEGs) compared to liver, both in response to fasting [42], and during LPS-induced inflammation [43]. Most recently, high-fat feeding has been shown to induce obesogenic gene expression changes in 4 murine tissues, with adipose tissue producing the second highest number of DEGs in the following order: skeletal muscle > adipose > liver > heart [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that transcription of hepatic Acc2 is markedly upregulated by increased food intake [45], insulin, and dexamethasone [46]. Unlike Acc1 which stimulates lipogenesis, Acc2 is known to inhibit lipolysis; and its structure has an N-terminal extension containing a mitochondrial-targeting motif which allows Acc2 to associate with Cpt1 on the outer mitochondrial membrane, thus regulating ß-oxidation at an early stage in the process [44]. High-fat diets and obesity have previously been associated with decreased expression of Ppargc1a, the dominant regulator of oxidative metabolism [41]; and whereas we have previously shown that Ppargc1a expression is reduced by intake of TFA compared to low-fat controls [9], we now demonstrate that levels of this transcription factor can be further attenuated by ASP + MSG exposure, both in the liver and particularly in the visceral adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were run in triplicate on the same reaction plate using the CFX96 Real-Time PCR Detection System (Bio-Rad) with β-actin as a loading control. Data analysis was performed in accordance with previously published work using the 2 −ΔΔCt method (Lee et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Several of these genes have not been implicated in cardiovascular diseases before. Tissue specific gene expression changes were also compared in obese animals [29]. In high-fat chow fed mice expression of several hundred genes is altered, although only a fraction of them is common between tissues.…”
Section: Hyperlipidemia Obesity and Statinsmentioning
confidence: 99%